Fluency in L2 learning and use - Lintunen, Pekka ;Mutta, Maarit ;Peltonen, Pauliina (Bristol : Multilingual Matters, 2020)
This book brings together theoretical and empirical approaches to second language (L2) fluency and provides a state-of-the-art overview of current research on the topic. The strength of the volume lies in its interdisciplinarity: the chapters approach fluency from non-traditional starting points and go beyond disciplinary boundaries in their contributions. The volume includes chapters investigating fluency from an L2 perspective and integrates perspectives from related fields, such as psycholinguistics, sign language studies and L2 assessment. The book extends the common foci and approaches of fluency studies and offers new perspectives that enable readers to evaluate critically existing paradigms and models. This encourages the development of more comprehensive frameworks and directs future L2 fluency research into new areas of L2 learning and use.
1.Defining fluency in L2 learning and use -- 2.What is fluency? : learner perceptions of the concept -- 3.Cognitive fluency in L2: what inaccuracies can reveal about processing and proficiency -- 4.Fluency in L2 learning -- 5.L2 fluency and writer proflles -- 6.Fluency in english as a Lingua Franca interaction -- 7.Fluency in sign language -- 8.Gestures as fluency-enhancing resources in L2 interaction: a case study on multimodal fluency -- 9.Fluency in language assessment -- 10.Fluency in evaluating and assessing translations -- 11.The effects of songs on L2 proficiency and spoken fluency: a pedagogical perspective -- 12.Synthesizing approaches to second language fluency: implications and future directions.
Includes index.
Keywords: FLUENCY (LANGUAGE LEARNING)